User interface technology for the hearing impaired people in Asia: a systematic literature review / Minmin Zhou and Kamal Sabran - Zhou, Minmin; Sabran, Kamal (2021)
The interface as a medium for information exchange allows users to achieve the purpose of interaction conveniently and effectively. It has profoundly affected many aspects of people's lives. As a large number of particular groups, the hearing impaired people can be helped to solve some practical problems in life by the development a targeted user interface for them. Since hearing impaired people generally have mild to severe hearing loss, they rely more on visual channels for information, so technology plays a crucial role in the development of user interfaces. Based on the literature review, this study explores what user interfaces have been developed by researchers focusing in Asia for the hearing impaired people. Besides, several technology types, including gesture recognition, speech recognition, wearable device, and sign language recognition, help hearing impaired users enhance their interactivity and understanding. This review shows that the future user interface needs to improve the traditional design methods and incorporate appropriate interactive technologies to maximize the learning and daily life of the hearing impaired people to provide positive results